2002
DOI: 10.1175/1520-0469(2002)059<0501:opoaai>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Atmospheric Aerosol in Maritime Environments

Abstract: Systematic characterization of aerosol over the oceans is needed to understand the aerosol effect on climate and on transport of pollutants between continents. We report the results of a comprehensive optical and physical characterization of ambient aerosol in 5 key island locations of the Aerosol Robotic Network (AERONET) of sun and sky radiometers, spanning over 2-5 years. The results are compared with aerosol optical depths and size distributions reported in the literature over the last 30 years. Aerosol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
304
2
18

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(372 citation statements)
references
References 105 publications
48
304
2
18
Order By: Relevance
“…1), and the dominance of sea salt could be important. However, Smirnov et al (2002Smirnov et al ( , 2011 studied optical properties in maritime environment and found that the AOD has a mean value of 0.07 with standard deviation of 0.03 to 0.05. This means that in a clean maritime environment, dominated by sea salt, the AOD is far below the limit for AERONET Level 2.0 data.…”
Section: Discussionmentioning
confidence: 99%
“…1), and the dominance of sea salt could be important. However, Smirnov et al (2002Smirnov et al ( , 2011 studied optical properties in maritime environment and found that the AOD has a mean value of 0.07 with standard deviation of 0.03 to 0.05. This means that in a clean maritime environment, dominated by sea salt, the AOD is far below the limit for AERONET Level 2.0 data.…”
Section: Discussionmentioning
confidence: 99%
“…Such a criteria ensures that the fine mode aerosols are mostly excluded from this analysis and the results are representative of nearly "pure" dust, even though the fine mode dust is also being excluded. Although sea salt aerosol is also mainly in the coarse mode and has smallÅngström exponent (∼0.3-0.7; Smirnov et al, 2002b), its contribution over these dust dominated sites is largely negligible. Both ALL and DU data are first sampled from the AERONET Version 2 quality assured Level 2 inversion data taken at 15 min time intervals.…”
Section: Aeronet Data and Analysis Methodsmentioning
confidence: 99%
“…Measurements of aerosol properties over the Mediterranean region have been carried out since the 1980s (Smirnov et al, 2002), but most of them were occasional and lasted only for short periods. Other measurements covered longer time periods (Cachorro et al, 2000;Formenti et al, 2001;Sabbah et al, 2001;Tanre et al, 2001;Gerasopoulos et al, 2003;Israelevich et al, 2003;Esposito et al, 2004;Pavese et al, 2009).…”
Section: Introductionmentioning
confidence: 99%